Determination of residual stress gradient in a Ti-stabilized austenitic stainless steel cladding candidate after carburization in liquid sodium at 500 °C and 600 °C. (December 2021) - Slim, Mohamed Fares; Geandier, Guillaume; Rouillard, Fabien; Malard, Benoit
Abstract: Non-destructive residual stress profile measurement with a micrometric depth resolution within the depth of carburized Ti-stabilized stainless steel cladding candidate was carried out by high-energy X-ray diffraction. The samples were carburized in carburizing nuclear liquid sodium at 500 °C and 600 °C for 1000 h. The full residual stress tensor profile was determined thanks to the estimation of the strain-free lattice parameter evolution using the carbon concentration profile measured by electron probe microanalysis and thermodynamic simulation. For the sample carburized at 500 °C, the residual stress genesis was governed by the carbon concentration within the steel and the formation of expanded austenite. For the sample carburized at 600 °C, the residual stress profile in the austenitic matrix depended on the precipitation of M23 C6 carbide. Stress relaxation was observed in the intragranular carburization zone. For the two temperatures, compressive residual stresses developed in the carburized zone and tensile stresses developed in the rest of the sample. Graphical abstract: Image, graphical abstract